Preventing Encounters between Children and Snakes - Steve A. Johnson; Martin B. Main (EDIS)
The most effective way to prevent a child from being bitten by a venomous snake at school or elsewhere is to prevent them from interacting with a snake. We provide measures that can be taken by schools to discourage snakes from coming onto school property and we provide a short educational program that teachers can give to students. This document is WEC 201, one of a 4-part series of the Department of Wildlife Ecology and Conservation entitled Dealing with Venomous Snakes in Florida School Yards, UF/IFAS Extension. Original publication date September 2005.